Design and Performance Prediction of an Axial Flow Compressor - H. ALjanabi, Shaker (Anbar Journal of Engineering Sciences, 2012)
The main objective of this paper is to create a method for designing and studying the performance of a multistage axial flow compressor. A mathematical methodology based on aerothermodynamics is used to study the on /off design performance of the compressor. Performance curves are obtained by changing the performance parameters in terms of design parameters (diffusion factor, solidity, Mach number, and inlet flow angle). Results show the great effect of diffusion factor on increasing efficiency than that of solidity, also the effect of both (diffusion factor and solidity) in increasing the amount of compression and efficiency of the compressor. Higher efficiency was found at the mean line between the root and tip of the blade. Best lift to drag ratio is found at inlet flow angle of (55o).